Phenotypic Spectrum of COL4A1 Mutations: Porencephaly to Schizencephaly. Issue 1 (7th December 2012) - Yoneda, Yuriko; Haginoya, Kazuhiro; Kato, Mitsuhiro; Osaka, Hitoshi; Yokochi, Kenji; Arai, Hiroshi; Kakita, Akiyoshi; Yamamoto, Takamichi; Otsuki, Yoshiro; Shimizu, Shin‐ichi; Wada, Takahito; Koyama, Norihisa; et al.
Abstract: Objective: Recently, COL4A1 mutations have been reported in porencephaly and other cerebral vascular diseases, often associated with ocular, renal, and muscular features. In this study, we aimed to clarify the phenotypic spectrum and incidence of COL4A1 mutations. Methods: We screened for COL4A1 mutations in 61 patients with porencephaly and 10 patients with schizencephaly, which may be similarly caused by disturbed vascular supply leading to cerebral degeneration, but can be distinguished depending on time of insult. Results: COL4A1 mutations were identified in 15 patients (21%, 10 mutations in porencephaly and 5 mutations in schizencephaly), who showed a variety of associated findings, including intracranial calcification, focal cortical dysplasia, pontocerebellar atrophy, ocular abnormalities, myopathy, elevated serum creatine kinase levels, and hemolytic anemia. Mutations include 10 missense, a nonsense, a frameshift, and 3 splice site mutations. Five mutations were confirmed as de novo events. One mutation was cosegregated with familial porencephaly, and 2 mutations were inherited from asymptomatic parents. Aberrant splicing was demonstrated by reverse transcriptase polymerase chain reaction analyses in 2 patients with splice site mutations. Interpretation: Our study first confirmed that COL4A1 mutations are associated with schizencephaly and hemolytic anemia. Based on the finding that COL4A1 mutations were frequent in patients with porencephaly and schizencephaly, genetic testing for COL4A1 should be considered for children with these conditions. ANN NEUROL 2013.